Bioastronomy and Life Exploration in the Universe: Conceptual Review and Educational Implications - Amrizal, Amrizal (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
Bioastronomy (astrobiology) explores the origin, evolution, distribution, and future of life in the universe and the search for life in extraterrestrial environments. This paper provides a conceptual review of key bioastronomy concepts—including biosignature definitions, habitability models, and both in situ and remote detection approaches—as well as examining pedagogical implications for formal and non-formal science teaching. The method is a systematic literature review of primary publications and reviews, along with a simple simulation to illustrate the application of a habitability index to a sample of hypothetical exoplanets. Findings show significant advances in biosignature assessment frameworks, life detection mission resources and strategies, and the growth of effective astrobiology education initiatives to enhance students’ interest and critical thinking skills. Simulation demonstrates strong variation in habitability indices influenced by stellar flux, equilibrium temperature, and water/biosignature scores. The discussion connects scientific results with educational practice: interdisciplinary astrobiology models offer rich contexts to develop science literacy, scientific reasoning, and analog-based laboratory experiences. Pedagogical recommendations include curriculum development, teacher training, and mission-based learning strategies. The article closes with ethical and communicative notes on claims of life detection and the need for robust evidence frameworks and communication protocols.